Design of Disaster Four-rotor Drone Control System Based on Fuzzy Self-turning PID Control - Zhou, Kairan (Transactions on Computer Science and Intelligent Systems Research, 2024)
Disasters often manifest as multifaceted crises that pose significant challenges for emergency responders, particularly when accessing hazardous environments such as fire scenes or chemically contaminated areas. The complexity of these situations necessitates the exploration of innovative solutions to augment the efficacy of rescue operations. In this context, the present study introduces a novel approach through the development of a disaster drone control system, predicated on the principles of fuzzy self-tuning control. This paper delineates the conceptual framework and architectural design of a fuzzy self-tuning Proportional-Integral-Derivative (PID) controller. It leverages fuzzy logic to enhance the precision of control actions by employing fuzzy rules, thereby facilitating a comparative analysis between traditional adaptive controllers and their fuzzy counterparts. Furthermore, this study embarks on a comprehensive examination of the current landscape, practical applications, and prospective advancements in the realm of disaster robotics. The findings underscore the superior accuracy and efficiency of the self-tuning PID control mechanism, which significantly expedites the identification of victims. Consequently, the deployment of disaster drones not only streamlines rescue operations by curtailing time and financial expenditures but also contributes to the broader objective of making rescue missions more manageable and effective.